WATER SUPPLY STATUS IN RURAL AREAS OF THE MEKONG DELTA AND DEVELOPMENT MEASURES - Lan Chi, Nguyen Thuy; Dao, Phan; Kyncl, Miroslav (GeoScience Engineering, 2018)
Rural people in the Mekong Delta (MD) use surface water from rivers and canals for daily activities; and in areas far from the canals, people use rainwater for cooking and drinking. In certain areas, people use shallow layered groundwater and deep layered groundwater from drilled wells 80m – 100m deep. The quality of water used in daily activities of rural people is almost uncontrolled. Somewhere water supply systems are used, but they have been built over many periods, certain ones for over 50 years ago, thus having a lot of damage and many deposits, causing loss of pressure and huge loss of water. The issue of repairing, replacing and installing more water supply networks in urban areas is facing lots of financial, technical difficulties. Keywords: surface water, Mekong Delta, water supply https://doi.org/10.2478/gse-2018-0005